2010
DOI: 10.1111/j.1463-5224.2010.00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative keratitis in thoroughbred racehorses in Japan from 1997 to 2008

Abstract: Ulcerative keratitis is the most frequent corneal and ocular disease of the racehorse in Japan. Careful observation of the eyes after racing is necessary as early diagnosis and treatment of corneal ulcers speeds healing. Many antibiotic have efficacy against the bacterial isolates, however, potent antibiotics should be reserved for the most severe corneal ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 16 publications
(34 reference statements)
7
63
4
1
Order By: Relevance
“…Pseudomonas spp. is a gram-negative bacillus, considered as one of the most virulent pathogens of the cornea, with a prevalence between 6 and 14% among the microorganisms identified in corneal ulcers of horses (SAUER et al, 2003;KELLER & HENDRIX, 2005;WADA et al, 2010;WADA et al, 2010). As expected, this genus was not isolated in the present study; although, it was previously identified in the eyes of horses without ophthalmic problems (ANDREW et al, 2003;VIDAL et al, 2010;JOHNS et al, 2011).…”
Section: Resultscontrasting
confidence: 39%
See 3 more Smart Citations
“…Pseudomonas spp. is a gram-negative bacillus, considered as one of the most virulent pathogens of the cornea, with a prevalence between 6 and 14% among the microorganisms identified in corneal ulcers of horses (SAUER et al, 2003;KELLER & HENDRIX, 2005;WADA et al, 2010;WADA et al, 2010). As expected, this genus was not isolated in the present study; although, it was previously identified in the eyes of horses without ophthalmic problems (ANDREW et al, 2003;VIDAL et al, 2010;JOHNS et al, 2011).…”
Section: Resultscontrasting
confidence: 39%
“…Lesions on the ocular surface, with the formation of ulcerative keratitis, are frequent in horses, due to their anatomic particularities and activity (WADA et al, 2010;KURODA et al, 2015) and the immediate use of antibiotics is recommended to prevent the establishment of infections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dentre os diversos fatores aos quais se atribui a elevada incidência de afecções corneais em equinos, elencamse o tamanho do bulbo do olho, seu posicionamento proeminente e lateralizado e atividades físicas dos equinos (STRUBBE et al, 2000;BAKER et al, 2008;WADA et al, 2010). Ainda, a superfície ocular encontrase constantemente exposta a bactérias e fungos.…”
Section: Desenvolvimentounclassified